Cutaneous Mastocytosis in Children: Is It Just a Skin Disease? - Tuğba Aktürk; Emine Türkkan; Deniz Özçeker (Çocuk Dergisi)
Introduction: Mastocytosis is characterized by the excessive proliferation and accumulation of mast cells in organs such as the spleen, liver, lymph nodes, skin, gastrointestinal tract, and bone marrow. Cutaneous mastocytosis, which is only presented with skin involvement, is frequently seen in childhood. Objective: It was aimed to determine the demographic and clinical characteristics of patients with cutaneous mastocytosis and the knowledge level of families about the disease, and to raise awareness about this disease. Material and Methods: The records of 25 cases with cutaneous mastocytosis were evaluated retrospectively and the knowledge levels of the families were measured with a questionnaire. Results: The mean follow-up period of 25 patients was 39 months. The most common type of the disease was urticaria pigmentosa (60%). Itching (n=14) was the most common symptom in patients. Only 2 patients were carrying adrenaline auto-injectors. While 60% of the families (n=15) had fears about the disease; of these 15 families, 53.3% (n=8) were afraid of the re-spread of the disease, 13.3% (n=2) turning of the disease into skin cancer, 13.3% (n=2) occupation of the internal organs, 13.3% (n=2) having a new attack, and 0.4% (n=1) re-forming of the spots. Conclusion: The cutaneous forms of mastocytosis are mostly observed in childhood, and systemic involvement is rare. Mastocytosis progresses with rashes in childhood and its findings are limited to the skin. Families should be better informed about mastocytosis and the need for patients to carry an adrenaline auto-injector due to the risk of attacks should be explained to them.